Zintl Phase Compounds Mg3Sb2−xBix (x = 0, 1, and 2) Monolayers: Electronic, Phonon and Thermoelectric Properties From ab Initio Calculations - Chang, Zheng; Ma, Jing; Yuan, Kunpeng; Zheng, Jiongzhi; Wei, Bin; Al-Fahdi, Mohammed; Gao, Yufei; Zhang, Xiaoliang; Shao, Hezhu; Hu, Ming; Tang, Dawei (Frontiers in Mechanical Engineering, 2022)
The Mg3Sb2-xBix family has emerged as the potential candidates for thermoelectric applications due to their ultra-low lattice thermal conductivity (κ_L) at room temperature (RT) and structural complexity. Here, using ab initio calculations of the electron-phonon averaged (EPA) approximation coupled with Boltzmann transport equation (BTE), we have studied electronic, phonon and thermoelectric properties of Mg3Sb2-xBix (x=0, 1, and 2) monolayers. In violation of common mass-trend expectations, increasing Bi element content with heavier Zintl phase compounds yields an abnormal change in κ_L in two-dimensional Mg3Sb2-xBix crystals at RT ( 0.51, 1.86 and 0.25 W/mK for Mg3Sb2, Mg3SbBi and Mg3Bi2). The κ_L trend was detailedly analyzed via the phonon heat capacity, group velocity and lifetime parameters. Based on quantitative electronic band structures, the electronic bonding through the crystal orbital Hamilton population (COHP) and electron local function analysis we reveal the underlying mechanism for the semiconductor-semimetallic transition of Mg3Sb2-xBix compounds, and these electronic transport properties (Seebeck coefficient, electrical conductivity and electronic thermal conductivity) were calculated. It was demonstrated that the highest dimensionless figure of merit ZT of Mg3Sb2-xBix compounds with increasing Bi content can reach 1.4, 0.2 and 0.6 at 700 K, respectively, and the diminished ZT value indicate that replacing heavier anion element in Zintl phase Mg3Sb2-xBix materials beyond common expectations, which provide a major insight for regulating thermoelectric performance without restricting conventional heavy elements theory.